ANALISIS TERANG AMORIS LAETITIA DAN ECCLESIA DOMESTICA PADA KONTEN YOUTUBE DESAHAN FOKUS MINOMARTANI - Stefanus Krisna Bayu Sulistyo; Rian Antony; Carolus Borromeus Mulyatno (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2023)
The rapid development of technology changes the warmth and intimacy between family members. Technology has succeeded in keeping everyone busy with their gadgets and the convenience of surfing virtual media. This situation results in a lack of warmth in the family. This study uses a qualitative method with a case study approach. This study aims to explore youtube content DESAHAN Minomartani Parish to proclaim the faith in the light of Amoris Laetitia and Ecclesia Domestica. This evangelization is also an effort to make Christian families feel increasingly warm in the family amid increasingly rapid technological developments. The research subject is the content of DESAHAN at Fokus Minomartani, which talks about family. This research is qualitative by applying a case study approach. The research subject is the content of DESAHAN in Minomartani Focus which raises about family. This research uses the theoretical framework of Pope Francis' thought in the documents of Amoris Laetitia and Ecclesia Domestica. The results showed three essential points. First, content with a family theme is always discussed every month. Second, a meditation on the family theme discusses messages relevant to the documents of Amoris Laetitia and Ecclesia Domestica. Third, content with a family theme is delivered to help families stay faithful to their marriage vows.